THE USE OF ICT IN ENGLISH TEACHING AT SMK (VOCATIONAL HIGH SCHOOL) REGENCY OF NGAWI DURING COVID-19 PANDEMIC - Amnan, Ari (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2020)
The objective of this research is to find out the English teaching during covid-19 pandemic. Due to the COVID-19 outbreak, all institutions of education in Indonesia held the teaching and learning from home as a way to reduce the outbreak the virus spread. The ministry of education has a partnership with some providers (online class) where teachers and students can utilize it as media freely, on the other hand, Teachers preferred to employ WhatsApp (WA) in conducting the class. Not all students have enough access to gain the facilities, such as the cost for buying internet data, mobile phone, and the reachable and stable signal for internet. Teachers and students may require eligible infrastructures to run the class properly.